(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to show that successful results can be obtained by combining the fractured parts over the operating table and fixing them with an anatomic plate in Mason type 3 - 4 multi-fragmented and / or displaced radial head fractures.